RELATIONSHIP OF SWITCHING COST TOWARDS SWITCH BARRIER IN TELECOMMUNICATION INDUSTRY IN JAKARTA - Mulyadi, Dedi; Fadli, Uus MD; Sinaga, Obsatar; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to measure the role of switching cost and the switching barriers in the telecommunication industry. The competition in telecommunication industry is very tough that lead service provider to compete against the limited market. One of the way to increase market share is through getting customer from competitor through attractive offering. This is a quantitative research that using questionnaire to collect data. 250 questionnaires but response rate is only 80%. The data analysis indicates that search cost and move in cost is significant towards the switching barrier. Telecommunication industry should consider the result in developing their marketing strategy and promoting their package for postpaid and prepaid services. Service provider in the industry should think of something in order to attract new customer and lock them for a certain numbers of period.